Formal language of Lanna Shop House's Façade in Lampang Old city, Thailand - Natthakit Phetsuriya (2018)
© Published under licence by IOP Publishing Ltd. This article aims to presents 'the formal architectural language of Lanna Designs" that is a linguistic paradigm for decrypt the linguistic system which is hidden in the Lanna façade style. Lanna Designs present an identity of vital ordered and crucial articulated formal language which inherently set of mathematical rules for the arrangement of ornaments. The scope of this article is attempted to the morphology of façades of the ten shop houses which located in Lampang Old city and have familiar proportion and style. In this article, the sampling of façade buildings required proportion as three-stall and two-story with familiar style. The morphology is described based on terms of a symbolic encoding system that is represented as graphically building grammar. The system helps to emphasize commonalities in façade languages and propose a prototype of identified Lanna façade design. This methodology might be the option for decrypt or study in every facades style.